2011
DOI: 10.3945/ajcn.110.009860
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived lactose intolerance results in lower intakes of calcium and dairy foods and is associated with hypertension and diabetes in adults

Abstract: Self-perceived lactose-intolerant respondents had a significantly lower calcium intake from dairy foods and reported having a significantly higher rate of physician-diagnosed diabetes and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 41 publications
3
60
0
6
Order By: Relevance
“…Moreover, proportionately more Hispanic and non-Hispanic white women of childbearing age reported consuming dairy products daily than do non-Hispanic blacks. Non-Hispanic black women reporting lower rates of dairy consumption is consistent with recent data on U.S. population reports of lactose intolerance (8). That study found that 76% of adults reporting to be lactose intolerant were female, and among females, 50% were non-Hispanic black, 30% non-Hispanic white, and 20% Hispanic.…”
Section: Iodine Status In Pregnant Women In Ncs and Nhanessupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, proportionately more Hispanic and non-Hispanic white women of childbearing age reported consuming dairy products daily than do non-Hispanic blacks. Non-Hispanic black women reporting lower rates of dairy consumption is consistent with recent data on U.S. population reports of lactose intolerance (8). That study found that 76% of adults reporting to be lactose intolerant were female, and among females, 50% were non-Hispanic black, 30% non-Hispanic white, and 20% Hispanic.…”
Section: Iodine Status In Pregnant Women In Ncs and Nhanessupporting
confidence: 89%
“…In the United States approximately 60% of iodine consumed comes from dairy products. The iodine is added to dairy products as a consequence of iodine added to cattle feed (6), or use of iodophor disinfectants in the milking process (7,8). Iodized salt accounts for a small amount of dietary iodine.…”
Section: Introductionmentioning
confidence: 99%
“…Use of iodized salt has declined with increasing attention to reducing salt consumption. Milk and milk products, an important source of iodine, may be avoided or not tolerated because of lactase deficiency, which is relatively common in the non-Hispanic black population [21]. We found that, in general, the median UI for US women of childbearing age was lower than the WHO cutoff point of 150 µg/l (fig.…”
Section: Discussionmentioning
confidence: 85%
“…Despite the increased consumption of whole grains, refined grains may be the traditional source of carbohydrates for and are preferably consumed by older Mexican Americans (10). This inverse relationship between dairy score and age may be partially due to older people’s misconception about lactose intolerance, which may result in lower dairy intakes (11). Regarding the association between sodium and age, previous research suggested mixed results (10,12).…”
Section: Discussionmentioning
confidence: 99%